PENERAPAN PENDIDIKAN JASMANI TERINTEGRASI TERHADAP GAYA HIDUP SEHAT DIKALANGAN PERSONEL ARFF DI BANDAR UDARA INTERNASIONAL MINANGKABAU PADANG (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the application of integrated physical education to the healthy lifestyle of Airport Rescue Fire Fighter (ARFF) personnel at Minangkabau Padang International Airport. The background is the importance of physical fitness in supporting rescue and emergency handling tasks. Based on observations and 2024 fitness tests, the majority of personnel have not met fitness standards and do not have a directed and continuous training program. This study used qualitative methods through observation, interviews and documentation. The results showed weaknesses in the training structure and the absence of physical training matriculation as the main obstacles. The proposed solutions included the preparation of training programs based on age groups, the habituation of a healthy lifestyle, and the establishment of a head of training position to manage the program. It was concluded that systematically integrated physical education can improve the fitness and work readiness of ARFF personnel. It is recommended that the airport implement a routine and sustainable fitness training and evaluation program to support flight safety.